The role of bovine preserved peritoneum in rats ventral hernia: a histological evaluation - Bastos,Eduardo Lemos de Souza (2006)
PURPOSE: To assess the role of preserved bovine parietal peritoneum as a material for hernia repair in a rat ventral hernia model. METHODS: An abdominal wall defect (15mm x 25mm) was created in Wistar male rats (n=40). Control animals (n=20) had the polypropylene (PP) mesh sutured into the defect, whereas bovine preserved peritoneum (BPP) was used in experimental group (n=20). After 7 and 28 days, the abdominal wall was taken off and histological studies of the amount of collagen by Sirius Red stain and morphometric evaluation consisted in quantitative analysis of the collagen by using specific software (Imagelab®). The Mann-Whitney, Kruskal-Wallis and ANOVA tests were applied for statistical analysis (pd"0.05). RESULTS: Histological examination revealed no difference between the BPP and PP groups (p = 0.55 NS). CONCLUSION: BPP is suitable for the closure of ventral hernias in rat model as shown by its morphological properties.